MANTEL BUMI - Gusti Maharani; Herlinda Mansyur; Susmiarti Susmiarti (SENDRATASIK UNP, 2013)
Abstract This article aims at revealing the image and reflection of a dance work entitled "Mantel Bumi" (earth’s crust). This dance tells about human’s greediness in exploiting the environment, which causes disasters to the human themselves. It causes global warming, resulting natural disasters and damaging human environment. Mantle or crust here is referred to the heat, the result of the environment destruction makes the earth is getting hotter for humans. This dance works with choreographic approached refers to Jacqueline Smith and La Meri, mixed in a dance work. The ending of the dance conveys the message that human greediness become a boomerang for the man himself.